Enterprising behaviour in the UK's National Health Service (NHS). Issue 9 (5th August 2014) - Exton, Rosemary
Abstract : Purpose: – This study by Rosemary Exton aims to examine the Improving Working Lives (IWL) programme and finds significant variation in outcomes between 11 National Health Service (NHS) Trusts. Each Trust was required to reach identical standards in improving HR practice over a set period. Achievement of the standards was validated by external peer review, and outcomes contributed significantly to overall performance ratings. Design/methodology/approach: – In each organisation, implementation was driven by a "lead" from line management, and three of these individuals form the focus of the study. Findings: – When visited 18 months after the end of the IWL initiative, most Trusts had failed to demonstrate any sustained change despite more than four years' effort. The ability to achieve effective and sustainable outcomes varies considerably even between NHS Trusts faced with comparable challenges in implementing nationally prescribed targets. This variance is explained in terms of an organisation's ability to generate structures, processes, individual competence and motivation to enable employees at all levels to act entrepreneurially, with the ability and legitimacy to achieve strategic goals by working creatively in the spaces between formal organisational structures. Originality/value: – While evidence highlights the importance of entrepreneurial behaviour in the transformation of the NHS, two of the "leads" studied demonstrated in different ways that managerial culture and working practices can inhibit the full engagement of staff, and the use of their knowledge and experience in service improvement and innovation.